Verifique que:

(pi)/(2) = 1 + sum_(n = 1)^(+ oo) (1.3 . 5 ... (2 n - 1))/(2.4 . 6 ... 2 n) (1)/(2 n + 1)

Passo 1

Aqui nós precisamos lembrar que:

a r c s e n x = x + sum_(n = 1)^(+ oo) (1.3 . 5 ... ( 2 n - 1 ))/(2.4 . 6 ... 2 n) (x^(2 n + 1))/(2 n + 1)

Sendo assim:

a r c s e n x = (pi)/(2)

x = s e n (pi)/(2) = 1

Se o x = 1 :

a r c s e n 1 = 1 + sum_(n = 1)^(+ oo) (1.3 . 5 ... ( 2 n - 1 ))/(2.4 . 6 ... 2 n) (1^(2 n + 1))/(2 n + 1)

(pi)/(2) = 1 + sum_(n = 1)^(+ oo) (1.3 . 5 ... ( 2 n - 1 ))/(2.4 . 6 ... 2 n) (1)/(2 n + 1)

Legal não foi?

Resposta

C o m o v i s t o a c i m a ‼

Ver Outros Exercícios desse livro